Health Education Innovation: Understanding the Role of Counseling via Video Media in Implementing Electronic Medical Records in Hospitals - Eko Prihati; Septo Pawelas Arso; Farid Agushybana; Taufik Muhtarom (Universitas PGRI Yogyakarta, 2024)
Electronic medical records (EMR) have made the management of patient health information more efficient by replacing manual record keeping. However, health workers still need to understand and apply RME well to get the maximum benefits. The role of counseling is needed for health workers in changing the use of manual media to digital. The research method uses scoping review. Based on the PubMed database as many as 88,041 articles with the keyword